IMPLEMENTATION OF THE ANDROID SOURCE CODE FOR “COHEN QUESTIONNAIRE – TO IDENTIFY THE LEVEL OF STRESS” - L.C. Dascalu; O. Chivu; C. Babiş; G. Iacobescu; A. Dimitrescu; E. Niculae (Fiabilitate şi Durabilitate)
This paper aims to present the study on the implementation of the source code for a Cohen questionnaire meant to detect stress level. The importance of this study consists in a unique mobile app for Cohen test. The results can be used for several research’s studies. We used instruments such us HTML, CSS, JavaScript, PHP, server web and MYSQL to develop the application for Android.The application is composed of 10 questions and at the end of test the users we received some recommendations to reduce stress at work.